Evolution Profiles of Different Corneal Parameters in Progressive Keratoconus. Issue 6 (June 2016) - Tellouck, Joy; Touboul, David; Santhiago, Marcony R.; Tellouck, Laury; Paya, Clement; Smadja, David
Abstract : Purpose: To analyze the evolution profiles of several corneal topographic and tomographic parameters in progressive keratoconus and compare them with the kinetics of evolution of anterior keratometry. Methods: One hundred nine eyes of 55 patients were prospectively enrolled and followed up every 3 months for at least 1 year. Forty-five corneal parameters were measured at each visit using a combined Placido-based and dual Scheimpflug imaging system. Percentage of progression between each visit was calculated for each parameter and comparisons were tested between the different variables. Results: At 1 year, 11% (12/109) of eyes progressed with an increase in maximum anterior keratometry of 1 D or more. Among these eyes, the posterior maximum keratometry and vertical corneal coma had a significantly higher percentage of progression ( P < 0.05) than the maximum anterior keratometry, 5.9%, 27%, and 3.2%, respectively, and occurred significantly earlier than the modifications of the anterior keratometry, at the third-, sixth-, and 12th-month visits, for vertical corneal coma, posterior keratometry, and anterior keratometry respectively. Conclusions: Modifications of the posterior surface and corneal vertical coma occurred earlier and were detectable before changes in the anterior keratometry readings in eyes with progressive keratoconus. These parameters may be relevant warning signs when monitoring progressive keratoconus.